Increasing the understanding of patterns of behaviours for alcohol in Wales using R - Hughes, Rhian; Patterson, Bethan; Withey, Clare (International Journal of Population Data Science, 2019)
Background Increasing the understanding of patterns of behaviours for alcohol are a key priority for Public Health Wales. We developed an interactive scrolling webpage to support this priority. Main Aim To develop a tool for understanding behaviour which brings together large amounts of information and presents it in a new and innovative way to inform and support decision makers. Methods Using the R programming language we developed an interactive scrolling webpage following an agile project management approach to involve key users. Users were engaged throughout the process, and outputs were produced in an iterative way to ensure the tool continued to meet the needs of the user. Results The interactive tool allows data interrogation and extraction and uses innovative techniques to display information without having to leave the tool. The profile includes an overview of the pattern of alcohol consumption and its impacts, along with the option to explore the data further at the local level. The information, presented across a series of tabs, allows users to navigate easily to the area of interest. Interactive elements, including dropdown selectors and checkboxes, were used to display additional information such as caveats and data sources. Conclusion Whilst R and agile project management require sufficient time investment, they were used successfully to disseminate public health knowledge in an informative way to increase the understanding of patterns of behaviours.